2011
DOI: 10.1038/bcj.2011.23
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the interaction of induction regimens with p-glycoprotein expression in patients with acute myeloid leukaemia: results from the MRC AML15 trial

Abstract: Retrospective analyses in non-randomised cohorts suggest that regimens containing fludarabine/Ara C and/or idarubicin/ara C may be more effective than daunorubicin/AraC (DA)-containing regimens in cases of acute myeloid leukaemia (AML) overexpressing p-glycoprotein (Pgp). We prospectively measured Pgp protein and function by flow cytometry in CD45-gated blasts from 434 AML15 trial patients randomised to remission induction therapy with two courses of FLAG-Ida or DA±etoposide (DA/ADE). In all, 34% were positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…3,4 In line with this notion, increased expression and functionality of ABC transporters on the surface of AML cells have been correlated with poor prognosis due to chemoresistance. 5,6 Notably, ABC transporters are frequently overexpressed in AML cases that exhibit additional risk factors, such as an unfavorable karyotype erlotinib was originally developed as an epidermal growth factor receptor (eGFR)-specific inhibitor for the treatment of solid malignancies, yet also exerts significant eGFR-independent antileukemic effects in vitro and in vivo. The molecular mechanisms underlying the clinical antileukemic activity of erlotinib as a standalone agent have not yet been precisely elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 In line with this notion, increased expression and functionality of ABC transporters on the surface of AML cells have been correlated with poor prognosis due to chemoresistance. 5,6 Notably, ABC transporters are frequently overexpressed in AML cases that exhibit additional risk factors, such as an unfavorable karyotype erlotinib was originally developed as an epidermal growth factor receptor (eGFR)-specific inhibitor for the treatment of solid malignancies, yet also exerts significant eGFR-independent antileukemic effects in vitro and in vivo. The molecular mechanisms underlying the clinical antileukemic activity of erlotinib as a standalone agent have not yet been precisely elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…There is some controversy regarding the role of MDR1 in AML chemoresistance. Although various studies have failed to detect any association between MDR1 expression and the response of AML patients to treatment with induction therapy [ 17 , 18 ], other reports have indicated that high MDR1 expression can predict the lack of response in these patients [ 19 , 32 , 33 ]. Our results support this concept.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ability of ABC pumps to transport idarubicin has not been clearly elucidated. Several studies have found an association between MDR1 overexpression and poor outcome after idarubicin treatment [ 16 ], while others describe no such relationship [ 17 , 18 ]. Our results in cells expressing MDR1 suggested that this pump can export doxorubicin, but not idarubicin, supporting the hypothesis that MDR1 upregulation in blasts from NR patients is involved in the mechanisms of chemoresistance developed by AML cells to overcome response to treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, high MDR1 expression has been considered as one of the most unfavorable prognostic factors for the responses of adult AML patients to induction regimens based on anthracyclines such as daunorubicin or idarubicin,74,75 but not mitoxantrone 76. Nevertheless, induction regimens containing idarubicin afford better CR rates than daunorubicin in AML patients expressing high MDR1 levels 77,78. By contrast, studies that have investigated the relationship between MDR1 over-expression and adverse treatment outcome have suggested that this connection is uncertain, at least in infant patients with AML 79.…”
mentioning
confidence: 99%